Correlation of sample‐to‐cut‐off ratio of anti‐SARS‐CoV‐2 IgG antibody chemiluminescent assay with neutralization activity: a prospective multi‐centric study in India. (28th June 2021) - Tiwari, Aseem K.; Negi, Gita; Jaiswal, Ram Mohan; Aggarwal, Geet; Yadav, Neeti; Kumar, Virendra; Kulathu, Krishnan
Abstract : Background and Objectives: There are limited published data on association of results from commercial serological anti‐SARS‐CoV‐2 IgG antibody CLIA (chemiluminescent immunoassay) assays with neutralizing antibodies. This study was undertaken with an objective to correlate sample‐to‐cut‐off (S/Co) ratio of CLIA antibody tests with inhibition activity, which may then serve as a valuable guide for labelling plasma as COVID convalescent plasma (CCP) for therapy and assessing vaccine efficacy. Materials and Methods: A total of 139 donor serum samples who were previously RT‐PCR positive and had recovered completely from COVID‐19 at least 28 days prior to collection of samples were recruited at three sites. The samples were analysed for S/Co ratio and per cent inhibition activity with VITROS SARS‐CoV‐2 IgG chemiluminescent assay and GenScript cPass SARS‐CoV‐2 Surrogate Virus Neutralization Test (sVNT) kit, respectively. Linear regression equation and receiver operating characteristic (ROC) curve were used to check the proposed model of comparing S/Co with per cent inhibition. Results: The results indicate very good correlation between the S/Co ratio of the chemiluminescent IgG assay and the neutralization activity depicted by per cent inhibition on sVNT assay. S/Co ratio of 4·04 (low‐titre) and 8·19 (high‐titre) correlated with 30% and 68% inhibition, respectively. Conclusion: Chemiluminescent SARS‐CoV‐2 IgG assay can be used as a semi‐quantitative test, with a cut‐off of >8·19S/Co ratio for selecting donors for convalescent plasma therapy and assessing efficacy of vaccination.